Modification of zeolitic imidazolate framework-8 with amine groups for improved antibacterial activity - Ahmad, N. (Elsevier Ltd, 2020)
The exploration of the metal-organic framework (MOFs) as a promising alternative for disinfection applications has not yet widely recognized. The flexibility of its structural diversity and large surface area with large pore size allows guest molecules to be stored and their ability to release metal ions has provided great prospect to generate high potent antibacterial activity for environmental applications. In this study, a rapid and straightforward post modification method for zeolitic imidazole framework 8 (ZIF-8) was developed through amine groups' introduction using ammonium hydroxide solution with improved antibacterial properties. The effect of different volume of ammonium hydroxide loadings towards ZIF-8 properties and its antibacterial activity was carefully examined. The result of Fourier transform infrared spectroscopy (FTIR) showed a successful modification of ZIF-8 with amine due to the presence of the N-H group; however, a significant decrease was observed in the BET surface area. The samples' antibacterial potency was tested against Escherichia coli ATCC 11229 and Staphylococcus aureus ATCC 6538 as Gram-negative and positive bacteria type strains, using disc diffusion (DDT) and minimum inhibitory concentration (MIC) testing, respectively. ZNH 20 was found to have the most potent antibacterial efficacy, with the MIC value needed to prevent bacterial growth two times lower than that of unmodified ZIF-8. The presence of positively charged amine groups promotes electrostatic adsorption of negatively charged membrane bacteria cells, which substantially enhanced the antibacterial activity of the modified sample. The synergistic effects of amine groups as well as zinc metal (Zn2+) in the modified ZIF-8 increased the antibacterial activity of the material and thus, making it suitable as antibacterial agents for water purification and biomedical applications. Â© 2020 Elsevier Ltd. All rights reserved.